Correlation of objectively measured light exposure and serum vitamin D in men aged over 60 years. Issue 1 (11th May 2016) - Fields, Alison J; Linnville, Steven E; Hoyt, Robert E
Diminished vitamin D is common among older individuals. Sunlight contributes more to vitamin D synthesis than diet or supplementation. This study examined associations between objectively measured light exposure, vitamin D serum levels, and bone biomarkers in 100 men aged over 60 years. Light exposure was measured in lux via Actigraph monitors for 1 week. Significantly, greater levels of vitamin D were observed in participants with higher light exposure. Seasonal differences in lux were also noted. Significant differences in bone markers were not found. Objective measurement of light exposure is an inexpensive, simple, and effective way to address vitamin D deficiency.